The Influence of Parent Socio-Economic Status And Use of Social Media on Student Consumptive Behaviour in The State Junior High School 1 Sidoarjo - Aziz, Muhammad Faris Abdil; Warsono, Warsono; Suratman, Bambang (International Journal for Educational and Vocational Studies, 2020)
The study was aimed to know information regarding the influence of parent socio-economic status and use of social media on student consumptive behaviour in State Junior High School 1 Sidoarjo. Research had been conducted on October 19th, 2019 at the nine grade class in State Junior High School 1 Sidoarjo. Respondents were asked to fill out a questionnaire which contains the socioeconomic status of parents, the use of social media and its influence on the consumption behavior of students. Based on the existing problems, this study was undertaken using quantitative research methods, because the data used based on the numbers then processed and analyzed using appropriate statistical models and using SPSS version 24. Researchers concluded the consideration described above, the initial phase for sampling using proportional random sampling technique. Total sample size in this study that as many as 40 students. Researcher used multiple linear regression analysis to determine the influence of socio-economic status of parents and the use of social media on consumptive behavior of students in the state junior high school 1 in Sidoarjo. The result of multiple linear regression analysis is β coefficient value on the socioeconomic status of parents at 0.930, indicating that any increase in the parent socio-economic status variable, then it will increase student consumptive behavior amounted to 0.930 and then β coefficient value on the use of social media at 0,438, indicating that any increase in the use of social media variable, then it will increase student consumptive behavior amounted to 0,438. In this partial effect, Parent Socio-Economic Status variable has a value of tcount 2.927 > ttable 2,021 and significance 0.006 < 0.05, then Ho is rejected and Ha accepted, which means partial socio-economic status of parents variable significantly influence consumer behaviour variables SMPN 1 Sidoarjo. The Uses of Social Media variable has a value of tcount 2,083 > ttable 2,021 and significance 0.044 < 0.05, then Ho is rejected and Ha accepted, which means in partial use of social media significantly influence student consumptive behaviour variables.